Pendampingan LDKS (Latihan Dasar Kepemimpinan Siswa) untuk Mengembangkan Karakter Kepemimpinan - Sriwahyuni, Tia Eka; Ahadiyah, Yustina Nur; Hadijah; Nafizah, Nurin (PT. Cahya Edupreneur Indonesia, 2025)
The LDKS (Basic Student Leadership Training) MA Sabilul Muttaqin assistance was held in the MA Sabilul Muttaqin Hall by lecturers and students of Islamic Education Management of the Hasan Jufri Bawean Islamic Religious Institute, aiming to increase students' understanding of the role of OSIM in shaping character and leadership. Through this activity, students learn about organizational management, communication, and discipline which are expected to support the formation of positive character. This activity took place involving participants from OSIM members, and students from class X and class XI. Overall, the LDKS activities in the room have gone well and have succeeded in achieving the main goal, namely the development of leadership, communication, and character skills of the participants. Some participants showed significant improvements in aspects of discipline, responsibility, and teamwork.